Correction: High-pressure structural phase transition and metallization in Ga2S3 under non-hydrostatic and hydrostatic conditions up to 36.4 GPa. Issue 10 (10th March 2021) - Yang, Linfei; Jiang, Jianjun; Dai, Lidong; Hu, Haiying; Hong, Meiling; Zhang, Xinyu; Li, Heping; Liu, Pengfei
Abstract : Correction for 'High-pressure structural phase transition and metallization in Ga2 S3 under non-hydrostatic and hydrostatic conditions up to 36.4 GPa' by Linfei Yang et al., J. Mater. Chem. C, 2021, 9, 2912–2918, DOI: ; 10.1039/d0tc06004f .